Effects of CO2, N2O, CH4 Emissions and Adjusted Net National Income on Food Security in 86 Countries - Aali-Bujari, Alí; Jiménez-Preciado, Ana Lorena; Venegas-Martínez, Francisco (International Journal of Energy Economics and Policy, 2025)
This paper examines the impact of climate change (measured as carbon dioxide, nitrous oxide, and methane emissions, as well as temperatures), arable land, and sustainable development (measured as Adjusted Net National Income, ANNI) on food security in 86 countries during 2012-2020. To this end, Granger non-causality in heterogeneous panels, static and dynamic panel data models, clusterization with elbow and silhouette analysis, as well as radar plot visualization. The Food Security Index (FSI) comes from Economist Impact (2022) and the rest of the variables from World Bank (2024). The main empirical result from panel data suggest that climate change has a negative effect on FSI, and ANNI measured as Gross National Income minus fixed capital consumption and natural resource depletion, used as a proxy of sustainable development, has a positive impact on FSI. Moreover, the cluster analysis complements the econometric analysis by identifying structural differences among countries that panel data models might overlook. Initially, two clusters are identified: one with only two members, China and the United States, and the other with the remaining countries. Subsequently, a cluster analysis is performed removing China and the United States to identify patterns in the rest of the countries. In this case, eight clusters are identified that share similar characteristics in the dynamics of all the variables under study, allowing for a more in-depth examination. There are now two clusters with only one member, Brazil and Russia. Other cluster contains only G7 countries. The largest cluster includes 31 countries. Finally, radar plots allow the specific characteristics of each of the eight groups to be visualized in relation to all the variables under study. Finally, the cluster analysis also offers important implications for sustainable policy design, suggesting the need for cluster-specific approaches rather than one-size-fits-all solutions.